A population pharmacokinetic model using allometric scaling for baricitinib in patients with juvenile idiopathic arthritis - Rodney L. Decker; C. Steven Ernest II; David B. Radtke; Rona Wang; Joana Araújo; Stuart Y. Keller; Xin Zhang (Wiley, 2024)
Abstract Baricitinib is approved for the treatment of rheumatoid arthritis (RA) in more than 70 countries, and juvenile idiopathic arthritis (JIA) in the European Union. Population pharmacokinetic (PK) models were developed in a phase 3 trial to characterize PK in pediatric patients with JIA and identify weight‐based dosing regimens. The phase 3, randomized, double‐blind, placebo‐controlled withdrawal, efficacy and safety trial, JUVE‐BASIS, enrolled patients (aged 2 to <18 years) with polyarticular course JIA. During a safety/PK period, baricitinib concentration data from age‐based dose cohorts were compared to concentrations from adult patients receiving 4‐mg QD. PK data were used to develop a population PK model with allometric scaling to determine a weight‐based posology in pediatric patients with JIA that matched the adult 4‐mg exposure. Baricitinib plasma concentrations from 217 pediatric patients were used to characterize PK. Based on the adult model, pediatric PK was best described using a 2‐compartment model with allometric scaling on clearance and volume of distribution and renal function (estimated with glomerular filtration rate [GFR], a known covariate affecting PK of baricitinib) on clearance. The PK modeling suggested the optimal dosing regimen based on weight for pediatric patients as: 2‐mg QD for patients 10 to <30 kg and 4‐mg QD for patients ≥30 kg. The use of a population PK model of baricitinib treatment in adult patients with RA, with the addition of allometric scaling for weight on clearance and volume terms, was useful to predict exposures and identify weight‐based dosing in pediatric patients with JIA.